PENETAPAN STATUS PENGGUNAAN BARANG MILIK NEGARA DALAM RANGKA OPTIMALISASI PENERIMAAN NEGARA - Hamdi Hamdi (Fiat Justisia: Jurnal Ilmu Hukum, 2015)
AbstractSOA Usage Status Determination Regulation in line with those mandated by Government Regulation Number 27 of 2014 on Management of State and Regional Assets has been regulated in Minister of Finance Regulation Number 246/PMK.06/2014 on Procedures for the Implementation of State Assets Utilization and Minister of Finance Regulation Number 41/PMK.06/2015 on Delegation of Certain Authority and Responsibility From State Assets Manager To State Assets User. The implementation of SOA Usage Status Determination in Regional Office Directorate General of State Assets Lampung Province and Bengkulu Province is not yet optimal because a little number of SOA status been defined. SOA optimization through utilization in order to gain state’s revenue through non-tax revenue is not the main goal, but the optimal use of SOA in order to support the implementation of the tasks and functions of Ministry/Agency. The implementation of State Asset Management Information System application was expected to support SOA management, especially related to supervision and control in the implementation of SOA Usage Status Determination.Keywords: State-Owned Assets, Usage Status Determination, SOA Utilization. Abstrakabstrak Peraturan SOA Status Penggunaan Penentuan sejalan dengan yang diamanatkan oleh Peraturan Pemerintah Nomor 27 2014 tentang Pengelolaan Barang Milik Negara dan Daerah telah diatur dalam Peraturan Menteri Keuangan Nomor 246/PMK.06/2014 tentang Tata Cara Pelaksanaan Penggunaan Barang Milik Negara dan Peraturan Menteri Keuangan Nomor 41/PMK.06/2015 tentang Pendelegasian Kewenangan dan Tanggung Jawab Tertentu dari Pengelola Barang Kkpada Pengguna Barang. Implementasi SOA Status Penggunaan Penentuan di Kanwil DJKN Provinsi Lampung dan Provinsi Bengkulu belum optimal karena sejumlah kecil status SOA telah ditetapkan. SOA optimasi melalui pemanfaatan untuk mendapatkan penerimaan negara melalui penerimaan negara bukan pajak bukanlah tujuan utama, tetapi penggunaan optimal dari SOA dalam rangka mendukung pelaksanaan tugas dan fungsi Kementerian/Lembaga. Penerapan aplikasi Sistem Informasi Negara Asset Management diharapkan untuk mendukung manajemen SOA, terutama terkait dengan pengawasan dan pengendalian dalam pelaksanaan SOA Status Penggunaan Penentuan.Kata Kunci: Aset Milik Negara, Penggunaan Status Penetapan, SOA Pemanfaatan